Efficacy in anterior uveitis of two known steroids and topical tolmetin. Issue 2 (February 1985) - Dunne, J A; Jacobs, N; Morrison, A; Gilbert, D J
Abstract : We have compared the anti-inflammatory efficacy of 5% tolmetin sodium dihydrate, 0.5% prednisolone disodium phosphate, and 0.1% betamethasone disodium phosphate in 71 consecutive patients presenting with acute endogenous non-granulomatous uveitis randomly assigned to one of these treatment groups. Inflammatory symptoms and signs were scored during the course of the 21-day trial period. There was no statistically significant difference in the effect on the signs or symptoms of the three drugs tested. 90% of the Betnesol (betamethasone sodium phosphate, benzalkonium chloride) treated group were clinically judged cured compared with 68% of the Predsol (prednisolone sodium phosphate, benzalkonium chloride) treated group, and 57% of the tolmetin treated group.